ANALISIS HUBUNGAN ANTARA HARGA SAHAM TERHADAP SUSTAINABILITY PERUSAHAAN SEKTOR INDUSTRI TELEKOMUNIKASI PERIODE 2011 – 2016 (STUDI KASUS PADA PT. XL AXIATA Tbk, PT INDOSAT Tbk, & PT TELEKOMUNIKASI INDONESIA (PERSERO) Tbk) - Reinandus Aditya Gunawan; Valencia Priska (Prosiding Working Papers Series In Management, 2018)
Telecommunication has an important role in people's lives because now most of all activities of people's lives, especially in running businesses depend on good communication and networking. Therefore, it is very important to pay attention to the sustainability of the telecommunication companies, especially for the stock investors who invest their funds in the telecommunication industry sector. A sustainable company will certainly survive in the ups and downs of business. One measurement to measure the sustainability of a company is using the ESG Score. The ESG score is generally divided into environment, social and governance and specifically divided into: resources, emission, environmental, workforce, human rights, community, product responsibility, management, shareholders, CSR. In this study, the relationship between telecommunication company stock returns and the ESG score variables specifically using Pearson correlation was sought. The results of this study are for XL Axiata, Tbk company stock returns do not have a relationship to the temporary ESG variables for Indosat, Tbk community variables have a significant negative correlation and for Telekomunikasi Indonesia (Persero) Tbk the emission variable has a positive correlation with stock returns. Keywords : Sustainability, ESG score, correlation.